Education on Self-Care Management as an Effort to Improve the Quality of Life of Hypertension Patients in Huta Durian Village, Bintang Bayu Subdistrict - Reni Aprinawaty Sirait; Naysillah Taqwima Ananis Sipayung (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Hypertension is one of the most prevalent non-communicable diseases and a major public health concern due to its association with cardiovascular disease, stroke, and kidney failure. Limited knowledge and poor self-care management among hypertensive patients may lead to uncontrolled blood pressure and an increased risk of complications. Therefore, educational interventions are needed to improve patients’ ability to manage their condition independently. This community service program aimed to improve the knowledge, skills, and self-care management behaviors of hypertensive patients in Huta Durian Village, Bintang Bayu District. The program was conducted through health education sessions, demonstrations, discussions, and hands-on practice related to hypertension management. A total of 30 hypertensive patients participated in the activity. Evaluation was carried out using pretest and posttest assessments to measure knowledge improvement, while observation was used to assess participants’ self-care management skills and behaviors. The results showed that the average knowledge score increased from 62.3 before the intervention to 86.7 after the educational program. Self-care management skills also improved, including the ability to measure blood pressure correctly (30.0% to 83.3%), understanding of a low-salt diet (40.0% to 86.7%), performing simple hypertension exercises (36.7% to 90.0%), understanding relaxation techniques (26.7% to 80.0%), and recording blood pressure monitoring results (23.3% to 83.3%). Positive behavioral changes were also observed in medication adherence, reduced salt intake, regular physical activity, routine blood pressure monitoring, and stress management. Self-care management education was effective in improving the knowledge, skills, and behaviors of hypertensive patients. This program can serve as a health promotion strategy to support hypertension control and improve community quality of life.